Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
Proceedings of the 2019 CHI Conference on Human Factors in Computing Systems 2019
DOI: 10.1145/3290605.3300428
|View full text |Cite
|
Sign up to set email alerts
|

Defending My Castle

Abstract: Home is a person's castle, a private and protected space. Internet-connected devices such as locks, cameras, and speakers might make a home "smarter" but also raise privacy issues because these devices may constantly and inconspicuously collect, infer or even share information about people in the home. To explore user-centered privacy designs for smart homes, we conducted a co-design study in which we worked closely with diverse groups of participants in creating new designs. This study helps fill the gap in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 91 publications
(27 citation statements)
references
References 30 publications
(30 reference statements)
0
22
0
Order By: Relevance
“…Prior work showed that sharing devices in multi-user smart homes is based on social relationships and sharing rules [19,21,34,65]. We show that not only rules for sharing, but also for guest interaction exist.…”
Section: Smart Speaker Interaction Etiquette As Access Controlmentioning
confidence: 76%
See 3 more Smart Citations
“…Prior work showed that sharing devices in multi-user smart homes is based on social relationships and sharing rules [19,21,34,65]. We show that not only rules for sharing, but also for guest interaction exist.…”
Section: Smart Speaker Interaction Etiquette As Access Controlmentioning
confidence: 76%
“…Visitors mainly expressed reluctance due to wanting to keep their requests private or not share their voice data. We suggest that this behaviour is influenced by their privacy perceptions, which in turn seem to be influenced by two factors identified by Yao et al: 1) perceived norms, namely their social relationship to the owner and their perceived trust towards the IPA provider, and 2) their privacy-seeking behaviour of protecting themselves by avoiding the device [65]. Most participants declared they would be comfortable using an IPA for basic entertainment purposes only and owners would find this an acceptable behaviour.…”
Section: Smart Speaker Interaction Etiquette As Access Controlmentioning
confidence: 80%
See 2 more Smart Citations
“…Fewer participants expressed privacy concerns around data ownership, which was around having control over the data collection and its use, as well as having the option to delete data [57]. Participants were less trusting of profit-making third-party organizations to work in the participants' interests, but did not seem to be overly concerned with the value of the data they shared.…”
Section: Privacy Concerns and Barriers To Data Sharing In Different Domainsmentioning
confidence: 99%